Planning Indicators for Improving the Quality of Life for Patients with Kidney Failure (A Study Applied to a Sample of Patients with Kidney Failure at Al-Shifa Complex in Gaza) - Almofty , Amjad M. (Jordan Journal of Social Sciences, 2023)
The study aimed to reach planning indicators to improve the quality of life for patients with kidney failure in the Gaza Strip by determining the level of quality of economic, social, health, family, and psychological life for patients with kidney failure.. The researcher employed a social survey methodology using a sample of kidney failure patients undergoing dialysis at Al-Shifa Medical Complex, numbering (107) patients, and the researcher used the quality-of-life scale tool prepared by him. The results of the study concluded that the psychological and economic quality of life for patients with renal failure was (low), by (52.3%) for the first and by (52.6%) for the second. The social, family and health life of patients with kidney failure came (medium) with a rate of (57%) for social life, (60%) for family life, and (68.3%) for healthy life. Finally, in light of the discussion of the results, the researcher reached a set of planning indicators, including that government and private institutions work to support this group of patients, increase their monthly income to suit family needs, activate networking and coordination between institutions to provide services to the patient and meet his diverse needs. The results further highlight the need to activating guidance and counseling programs, directing them to learn problem-solving skills, professional counseling, case management, and providing psychological and social support programs